Beyond NAMs versus animal models: Context of use as the governing framework for integrated nonclinical strategies in drug development - Stefano Gaburro; Brian Berridge; Nicholas W. Kelley; Eckhard von Keutz; Marc Ferrer; Clive Roper; Michael J. Fossler; Jeffrey J. Bajramovic; Jean-Pierre Valentin; Timothy McGovern; Todd Bourcier; Ronald L. Wange; et al. (Regulatory Toxicology and Pharmacology, 2026)

Combining seepage meters and amphibious electric resistivity tomography to investigate pathways of submarine groundwater discharge - Marc Diego-Feliu; Maria Munoz-Pinyol; Jose Tur-Piedra; Michela Trabucchi; Aaron Alorda-Kleinglass; Raquel González-Fernández; Núria Ferrer; Bella Almillategui; Audrey Sawyer; Carlos René Green-Ruiz; Juanjo Ledo; Valentí Rodellas; et al. (Science of The Total Environment, 2025)

Distribution and habitat use by the Audouin's Gull (Ichthyaetus audouinii) in anthropized environments - Aleix Ferrer Vilaplana; Isabel Afán; Daniel Oro; Juan Bécares; Marc Illa; Marcel Gil; Albert Bertolero; Manuela G. Forero; Francisco Ramírez (Science of The Total Environment, 2024)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Current Status of Forecasting Toxic Harmful Algae for the North-East Atlantic Shellfish Aquaculture Industry - Jose A. Fernandes-Salvador; Keith Davidson; Marc Sourisseau; Marta Revilla; Wiebke Schmidt; Dave Clarke; Peter I. Miller; Paola Arce; Raúl Fernández; Luz Maman; Alexandra Silva; Callum Whyte; et al. (Frontiers in Marine Science, 2021)
Across the European Atlantic Arc (Scotland, Ireland, England, France, Spain, and Portugal) the shellfish aquaculture industry is dominated by the production of mussels, followed by oysters and clams. A range of spatially and temporally variable harmful algal bloom species (HABs) impact the industry through their production of biotoxins that accumulate and concentrate in shellfish flesh, which negatively impact the health of consumers through consumption. Regulatory monitoring of harmful cells in the water column and toxin concentrations within shellfish flesh are currently the main means of warning of elevated toxin events in bivalves, with harvesting being suspended when toxicity is elevated above EU regulatory limits. However, while such an approach is generally successful in safeguarding human health, it does not provide the early warning that is needed to support business planning and harvesting by the aquaculture industry. To address this issue, a proliferation of web portals have been developed to make monitoring data widely accessible. These systems are now transitioning from “nowcasts” to operational Early Warning Systems (EWS) to better mitigate against HAB-generated harmful effects. To achieve this, EWS are incorporating a range of environmental data parameters and developing varied forecasting approaches. For example, EWS are increasingly utilizing satellite data and the results of oceanographic modeling to identify and predict the behavior of HABs. Modeling demonstrates that some HABs can be advected significant distances before impacting aquaculture sites. Traffic light indices are being developed to provide users with an easily interpreted assessment of HAB and biotoxin risk, and expert interpretation of these multiple data streams is being used to assess risk into the future. Proof-of-concept EWS are being developed to combine model information with in situ data, in some cases using machine learning-based approaches. This article: (1) reviews HAB and biotoxin issues relevant to shellfish aquaculture in the European Atlantic Arc (Scotland, Ireland, England, France, Spain, and Portugal; (2) evaluates the current status of HAB events and EWS in the region; and (3) evaluates the potential of further improving these EWS though multi-disciplinary approaches combining heterogeneous sources of information.

Adenosine A2A-Cannabinoid CB1 Receptor Heteromers in the Hippocampus: Cannabidiol Blunts Δ9-Tetrahydrocannabinol-Induced Cognitive Impairment - Ester Aso; Víctor Fernández-Dueñas; Marc López-Cano; Jaume Taura; Masahiko Watanabe; Isidre Ferrer; Rafael Luján; Francisco Ciruela (Molecular Neurobiology, 2019)

Blood chemistry values in nestlings of Rockhopper Penguins (Eudyptes chrysocome): the effect of sex and body condition - Virginia Morandini; Miguel Ferrer; Lynelle Perry; Marc Bechard (Polar Biology, 2018)

Factors affecting plasma chemistry values of the black-browed albatross Thalassarche melanophrys - Miguel Ferrer; Virginia Morandini; Lynelle Perry; Marc Bechard (Polar Biology, 2017)

Effects on postural oscillation and memory functions of a single dose of zolpidem 5mg, zopiclone 3.75mg and lormetazepam 1mg in elderly healthy subjects. A randomized, cross-over, double-blind study versus placebo - Danile Bentu-Ferrer; Herv Allain; Antoine Tarral; Jean-Marc Gandon (European Journal of Clinical Pharmacology, 2003)